Maternal body mass index and cervical length among women with a history of spontaneous preterm birth†. (3rd March 2020) - Venkatesh, Kartik K.; Manuck, Tracy A.
Abstract: Objectives: To evaluate whether women with a prior spontaneous preterm birth (SPTB) with a higher body mass index (BMI) have a lower risk of a shortened cervix in a subsequent pregnancy. Study Design: A secondary analysis of the Maternal-Fetal Medicine Units Network RCT of omega-3 fatty acid supplementation for recurrent SPTB prevention. All women had ≥1 prior SPTB <37 weeks, a singleton pregnancy, and initiated 17-alpha hydroxyprogesterone caproate(17-OHPC). The primary exposure was pre-pregnancy BMI. The primary outcome was the shortest transvaginal cervical length <30 mm. Results: Of the 356 women with a prior SPTB receiving 17-OHPC and a cervical length available, 108 (30%) were overweight and 103 (29%) obese; 12% had a cervical length <30 mm. Fewer overweight/obese women had a shortened cervix compared to normal-weight women (43 versus 57%; odds ratio: 0.47 [95%CI: 0.25–0.89]). After adjusting for maternal age, number of prior SPTBs, and tobacco use, overweight/obese women were less than half as likely to have a shortened cervix compared to normal-weight women (adjusted odds ratio: 0.46, 95%CI: 0.24–0.89). Conclusions: Overweight and obese women with a prior SPTB receiving 17-OHPC have longer cervical lengths compared to normal weight women, and this finding could explain a possible mechanism between the decreased rate of SPTB and larger BMI.